Legislative basis of the legislation of the state authorities - Vasilevich, Grigory A. (Journal of the Belarusian State University. Law, 2019)
The article analyzes the legislation that creates the basis for the standard-setting activities of public authorities. Special attention is paid to the provisions of the Law «On normative legal acts» which came into force from 1 February 2019. It is emphasized, along with the Constitution, the importance for the formation of such an important part of the national legal system as acts of legislation. While appreciating the law in general, a number of ideas for its further improvement were expressed. In particular, on the definition of a higher role of special laws, on the careful forecasting of the consequences of the regulatory impact of acts, their economic assessment, on the definition of the status of concepts. Programs approved by public authorities degree of commitment and responsibility for non-compliance, etc., the necessity of preparation and adoption of more extensive in its content, the laws that there is less need to engage in legislative rulemaking, filling in gaps or implementing the laws contained in the act of blanket rules. The law, unlike by-laws, is known to regulate the most significant public relations. The possibility of wider use of information technologies in the law-making process is emphasized which are able to radically affect the relations between the state and the individual, to promote the expansion of rights and freedoms, to provide more economical (effective) legal regulation of public relations.